Paul Knitter's Soteriocentrism Study of the GPIB's Formula of Understanding of Faith regarding Safety for All Creation - Bail, Naomi Lestari; Quartyamina, Cindy; Lalenoh, TM Ebenheser (TELEIOS: Jurnal Teologi dan Pendidikan Agama Kristen, 2025)
Abstract:Human life with God's other creations has a mutually beneficial relationship, but humans often cause crises that threaten the safety of other creations due to anthropocentric thinking. The author uses Paul Knitter's theory of soteriocentrism, which affirms the primacy of the cosmic aspect while emphasizing a multi-normative approach or correlational dialogue in interfaith cooperation based on soteriocentrism, namely efforts to take global responsibility for the welfare of humans and the environment. The responsibility to improve and prevent the crisis requires awareness and real action from every human being, including church members, including the Protestant Church in Western Indonesia (GPIB). This research uses a library research approach and interviews. The results showed that GPIB has genuinely lived the work of God's salvation bestowed to save all creation and believes in the importance of working with all parties to realize the wholeness of all creation. Thus, GPIB has implemented the principle of soteriocentrism, whose indicators are contained in the Confession and GPIB's work program, which is seriously oriented towards the salvation of creation. The basic formulation of the good Confession can strive to continue to be aligned with the practice of sustainable action that does not stop at implementing an activity or work program for environmental care alone. Instead, action is seriously directed at ensuring that awareness of the importance of seeking the salvation of all creation is strongly internalized in all members of the congregation and GPIB ministers.